The lower content of mineral-complexing compounds favored the in vitro and in vivo iron bioavailability of biofortified cowpeas - Letícia de Souza Scherrer Medeiros; Mariana Grancieri; Cíntia Tomaz Sant'Ana; Manuela Cristina Pessanha de Araujo Santiago; Leon Brunhara da Silva; Raymond P. Glahn; Neuza Maria Brunoro Costa (Journal of Functional Foods)
This study aimed to evaluate in vitro and in vivo iron bioavailability of biofortified cowpeas (Vigna unguiculata (L) Walp) (Aracê, Xiquexique and Tumucumaque), compared to a conventional cultivar (Pajeú). In vitro bioavailability was evaluated in Caco-2 cells. For the in vivo study, 40 male Wistar rats were induced to anemia during 21 days (depletion phase), then, in repletion phase (14 days), the animals received as iron source (12 ppm): ferrous sulfate; Pajeú; Xiquexique, Aracê; or Tumucumaque. Pajeú had higher levels of complexing compounds than the biofortified cultivars. In Caco-2 cells, the cellular iron uptake index was higher for biofortified cowpeas, particularly Tumucumaque. Concerning the in vivo study, Tumucumaque group had the best hemoglobin regeneration efficiency and relative biological value, and improved colon crypt size. Then, the iron bioavailability was higher in the biofortified cowpeas, especially Tumucumaque, possibly due to the lower content of mineral-complexing compounds and improvement of absorptive area. This work provides important information to support strategies to combat iron deficiency.